OUTPATIENT REHABILITATION OF CHILDREN WITH HEALTH DEVIATIONS - V.V. Polunina; A.S. Suyundukova; E.Yu. Sergeenko; S.V. Pavlova; A.A. Ipatov (Вопросы современной педиатрии, 2011)
Outpatient help to underage population is leading priority for the general healthcare system. The main task of a child policlinic is prevention and early detection of pathologies, and decreasing of rates of illness and child mortality. Complex rehabilitation of children helps improve basic health indexes in underage population. The article displays effectiveness of complex program of medical and social rehabilitation of children with health deviations on the outpatient basis.Key words: medical and social rehabilitation, reflex therapy, child, sickness rate. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 14–19.)